Constructing Cultural Identity. Michael Poerner about Chinese Perspectives on Intercultural Business Communication (KULT_online, 2013)
The status of China as an economic powerhouse is originally based on investments made by western companies in mainland China. But this situation is about to change. Meanwhile a number of Chinese companies are expanding into industrialized (western) nations encountering severe problems of intercultural confrontation. By considering these new frame conditions Michael Poerner shows how Chinese academics and the media discuss cultural difference in the field of economics. In his doctoral thesis he analyses patterns of Chinese identity constructions, self perception, and the perception of "western culture". In addition the author regards the international academic discourse on "Asian communication" as depending on a rather simplified model of culture lacking valid data and a modern theoretical foundation.